2008
DOI: 10.4012/dmj.27.710
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of B-type carbonate apatite blocks by the phosphorization of free-molding gypsum-calcite composite

Abstract: B-type carbonate apatite (CO3Ap) block may be an ideal artificial bone substitute because it is closer in chemical composition to bone mineral. In the present study, the feasibility to fabricate CO3Ap blocks was investigated using compositional transformation, which was based on the dissolution-precipitation reaction of a gypsum-calcite composite with freemolding behavior. For the compositional change, or phosphorization, gypsum-calcite composites of varying CaCO3 contents were immersed in 1 mol/L (NH4)3PO4 aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…On the other hand, there was a lack of formability, because the shape of CO3Ap block was dependent on the precursor prepared by powder compacting device. In order to improve the formability, Zaman et al have reported that calcite block, which includes gypsum as bonding material, could be applied as precursor 13) . With this method, since the precursor block can be formed by gypsum setting and not by pressing, various shapes could be obtained using molds with various shapes for precursor setting.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there was a lack of formability, because the shape of CO3Ap block was dependent on the precursor prepared by powder compacting device. In order to improve the formability, Zaman et al have reported that calcite block, which includes gypsum as bonding material, could be applied as precursor 13) . With this method, since the precursor block can be formed by gypsum setting and not by pressing, various shapes could be obtained using molds with various shapes for precursor setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the solubility of calcite is lower when compared with that of gypsum. Therefore, some calcite remained unreacted when a mixture of gypsum and calcite was used as a precursor 8) . In contrast, pure set gypsum with the same composition was used as a precursor in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It also should have low solubility in the solution to allow a balanced dissolution and precipitation process. To date, calcite (CaCO 3) , α-tricalcium phosphate, a mixture of gypsum and calcite were proposed as precursors [7][8][9][10] . Among the array of precursors, gypsum is unique because it has self-setting ability, which allows it to be molded and shaped to how we would like it to be at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These calcium phosphate compounds are classified in this paper as that the materials of HAP are 'HAP series', those of -TCP, -TCP and TTCP are 'other calcium phosphate series'. HAP, -TCP, -TCP and TTCP made by our technology were utilized as reagents and raw materials for commercial products [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%